2003
DOI: 10.1200/jco.2003.02.042
|View full text |Cite
|
Sign up to set email alerts
|

Minidose Warfarin Prophylaxis for Catheter-Associated Thrombosis in Cancer Patients: Can It Be Safely Associated With Fluorouracil-Based Chemotherapy?

Abstract: A high incidence of INR abnormalities was observed in our cohort of patients, especially those treated with FOLFOX regimen. Clinicians should be aware of this interaction and should regularly monitor the prothrombin time in patients receiving warfarin and FU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0
6

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 35 publications
0
52
0
6
Order By: Relevance
“…Supporting this notion, we found that the vast majority of recurrent VTEs were treated with LMWH monotherapy. The desire to avoid drug-drug interactions in patients receiving chemotherapy and warfarin may also explain in part the preference for LMWH monotherapy in these patients [20,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting this notion, we found that the vast majority of recurrent VTEs were treated with LMWH monotherapy. The desire to avoid drug-drug interactions in patients receiving chemotherapy and warfarin may also explain in part the preference for LMWH monotherapy in these patients [20,24].…”
Section: Discussionmentioning
confidence: 99%
“…This is an important outcome because cancer patients with VTE are more likely than a non-cancer patient to experience a recurrent VTE, and recurrent VTE is a substantial burden on both the patient and the healthcare system [19]. Furthermore, warfarin therapy interacts with many chemotherapy agents [20] and INR control is more difficult in cancer patients [21]. Cancer patients frequently require invasive procedures, and coordination of warfarin therapy interruption for these procedures is notoriously challenging [5].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed thromboprophylaxis appears to be safe, even in patients with haematological malignancies who often have concurrent severe thrombocytopenia (Boraks et al, 1998;Cortelezzi et al, 2005). However, it is important to recognise that minidose warfarin (1 mg day À1 ) can have a significant effect on the prothrombin time in cancer patients (Heaton et al, 2002;Masci et al, 2003;Mismetti et al, 2003;Magagnoli et al, 2005). The aetiology of this increased prothrombin time is multifactorial, and includes anorexia and liver metastases (Magagnoli et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of some studies that showed that minidose of warfarin (1 mg/ day) reduces catheter-related thrombosis without inducing alterations in the prothrombin time (PT) or activated partial thromboplastin time (aPTT) or causes bleeding [8][9][10][11], all patients undergoing high-dose chemotherapy were given prophylaxis with minidose warfarin in our bone-marrow transplantation (BMT) unit.…”
Section: Introductionmentioning
confidence: 99%